Strategi pembelajaran bahasa berbantukan kecerdasan buatan - Syarifuddin Tundreng; Kadaruddin Kadaruddin; Rais Abin; Hariadi Syam; Alifiah Pratiwi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The use of Artificial Intelligence (KB) has experienced rapid development in various fields, including education and learning. This article discusses artificial intelligence-assisted language learning strategies. The main objective of this strategy is to increase the efficiency and effectiveness of the language learning process by utilizing family planning technology. This article outlines various approaches that can be used in the implementation of KB-assisted learning strategies, including automated text analysis, personalized learning, adaptive feedback, language error detection, and automatic translation. The advantages and challenges of each approach are discussed in depth, as well as their potential impact on language learning outcomes. This study adopts a literature analysis approach to investigate language learning strategies assisted by artificial intelligence. The steps taken in this study include the identification and collection of relevant literature sources, as well as critical analysis of the information found. By combining the advantages of family planning technology with the principles of language learning, it is hoped that this strategy can pave the way to a more interactive, adaptive, and efficient learning experience